Study of catalytic properties of zirconium-aluminium oxide and zirconium-containing calcium aluminate materials in the process of methanol dehydration - M. A. Kruglova; M. P. Yaroshenko; S. N. Antonyuk; E. Z. Golosman (Тонкие химические технологии)
The zirconium-aluminium oxide and zirconium-containing calcium aluminate materials of different composition were prepared. Their activity in the process of methanol dehydration was investigated. It was found that their activity depends on the acidic properties of the surface of the synthesized materials, which in turn is determined by the ratio of components. It was concluded that the proposed systems can be promising catalysts for obtaining dimethyl ether.